2015
DOI: 10.7314/apjcp.2015.16.8.3339
|View full text |Cite
|
Sign up to set email alerts
|

Single Nucleotide Polymorphisms in the Gc Gene for Vitamin D Binding Protein in Common Cancers in Thailand

Abstract: Background: This case-control study aimed to determine if there were any associations between the two single nucleotide polymorphisms (SNPs) in Gc, rs7041 (Asp416Glu) and rs4588 (Thr420Lys) and 3 common cancers (breast, lung and colorectal) in Thai patients. Materials and Methods: Two hundred and eighty two colorectal, 101 breast and 113 lung cancer patients were recruited from one institute during 2011-2013. The controls were age-matched volunteers who had a negative history of index cancers. In addition, vit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
12
0
3

Year Published

2016
2016
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(17 citation statements)
references
References 29 publications
2
12
0
3
Order By: Relevance
“…Previous lung cancer studies have reported various results [65,66]. In the current study, it is shown that slight increases in NSCLC risk with rs7041 polymorphisms for rs7041 was a common nonsynonymous SNP in the GC gene.…”
Section: Discussionsupporting
confidence: 53%
“…Previous lung cancer studies have reported various results [65,66]. In the current study, it is shown that slight increases in NSCLC risk with rs7041 polymorphisms for rs7041 was a common nonsynonymous SNP in the GC gene.…”
Section: Discussionsupporting
confidence: 53%
“…This diversity together with low number of affected patients could be a reason why we did not show any associations of tested polymorphisms with a mortality risk due to neoplasms, although such connections were described [35, 48, 49]. …”
Section: Discussionmentioning
confidence: 84%
“…Yapılan çalışmalarda alel 2'nin makrofaj etkinleştirici özelliğinin daha az olduğu ve bunun sonucunda alel 2'yi taşıyan bireylerin makrofaj işlevinin daha düşük olduğu bildirilmiştir. Bugüne kadar yapıl-mış olan ve VDBP'yi kodlayan gendeki bu polimorfizmlerin (rs7041 ve rs4588) akciğer, [14] meme [15] ve prostat [16] kanseri ile ilişkili olduğunu öne süren çalışmalar olduğu gibi, GC polimorfizmlerinin prostat, [17] kolorektal kanser, [18,19] bazal hücreli karsinom [20] ve melanoma (sadece rs7041 incelenmiş) [21] ile ilişkisi olmadı-ğını bildiren çalışmalar da bulunmaktadır. Literatürde bugüne kadar VDBP polimorfizmi ile akciğer kanseri arasındaki ilişkiyi araştıran çalışma sayısı çok kısıtlı-dır.…”
Section: Bulgularunclassified
“…Literatürde bugüne kadar VDBP polimorfizmi ile akciğer kanseri arasındaki ilişkiyi araştıran çalışma sayısı çok kısıtlı-dır. Maneechay ve ark.nın [14] yapmış olduğu çalışmada rs7041 (416 GAT>GAG (Asp>Glu) polimorfizminin akciğer kanseri ile ilişkili olduğu, 113 hastadan 61'inin TG genotipine sahip olduğu, bunun da akciğer kanseri ile ilişkili olduğu gösterilmiştir (p=0.037). rs7041 ve rs4588'deki tek nükleotid polimorfizmleri kombine olarak incelendiğinde ise 1F-2 (TT-CA) genotipine sahip olmanın akciğer kanserine karşı belirgin bir koruyucu etkisi olduğu görülmüştür (p=0.014).…”
Section: Bulgularunclassified
See 1 more Smart Citation